Sex- and age- specific normal values with threshold-based trabeculae quantification. (4th February 2022) - Grebur, K; Gregor, ZS; Kiss, AR; Szabo, LE; Toth, A; Horvath, M; Dohy, ZS; Merkely, B; Vago, H; Szucs, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): ÚNKP-19-3-II New National Excellence Program of the Ministry for Innovation and Technology National Research, Development and Innovation Office of Hungary (NKFIA; NVKP_16-1-2016-0017 National Heart Program) Thematic Excellence Program (Tématerületi Kiválósági Program 2020-4.1.1-TKP2020) The threshold-based (TB) trabeculated and papillary muscle mass (TPM) quantification method for cardiac MRI (CMR) calculates different values than conventional contouring techniques. We aimed to identify the sex- and age-related normal reference ranges for left ventricular (LV) myocardial mass values, volumetric and functional parameters and the correspondence of these parameters using the TB method. Healthy European adults (n = 200, age: 39.4 ± 12 years, males: 100) were examined with CMR and evaluated with a TB postprocessing method. They were stratified by sex and age (Group A: 18-29, Group B: 30-39, Group C: 40-49, Group D: >50 years). The calculated parameters were indexed to body surface area (i). The normal reference ranges for the studied parameters were assessed in each age group. Significant biometric differences in LV parameters and mass-to-volume ratios were found between males and females, and the left ventricular compacted myocardial mass (LVCMi) and TPMi differences remained significant after stratification by age. Unlike other LV volumetric and functional parameters and mass-to-volume ratios, the TPMi, the LVCMi and the TPMi-to-LVCMi ratio did not differ among age groups in males or females. This finding was strengthened by the lack of correlation between TPMi and age. Age- and sex-related normal reference ranges for LV volumetric and functional parameters and LVCMi and TPMi values were established using a TB postprocessing method. TPMi, LVCMi and their ratio did not change over time. The TPMi-to-LVCMi and the mass-to-volume ratios might have clinical utility in the differential diagnosis of conditions with LV hypertrabeculation.